The application of vernacular Australian environmental design principles in Glenn Murcutt’s architecture - Lecaro, Mauricio; Lau, Benson; Rodrigues, Lucelia; Jarman, Dik (Springer, 2017)
Glenn Murcutt is recognised as one of the most influential architects of the last few decades. His design philosophy, environmental awareness and in-depth understanding of the Australian context and vernacular architecture, have made him one of the leaders of critical regionalism worldwide. His buildings not only provide shelter, but also offer comfort with lower environmental impacts through simple, yet creative design solutions. Although Murcutt’s architecture is well documented, limited evidence-based research has been undertaken to study his approach to design and how this has a direct influence on visual and thermal comfort in his buildings; this paper aims to fill this gap.